Vibrational spectra of magnesium oxalates - D'Antonio, Maria C. (2010)
The infrared and Raman spectra of anhydrous MgC2O4 as well as those of the two polymorphic forms of the dihydrated oxalate, α-MgC2O4·2H2O and β-MgC 2O4·2H2O, were recorded and discussed on the basis of their structural peculiarities and in comparison with the spectra of natural α-MgC2O4·2H2O (the mineral glushinskite). Some comparisons between these polymorphs and with other, previously investigated, oxalate complexes were made. The IR spectra of partially deuterated samples of α-MgC2O4· 2H2O were also discussed, reinforcing some of the performed assignments.